DESIGNING OF LIGHTWEIGHT CONCRETE WITH SECONDARY RESOURCES IN DNIPROPETROVSK REGION - Netesa, M. I.; Palanchuk, D. V. (Science and Transport Progress, 2010)
The problems of utilization of the local industry after-products in the easy concretes and efficiency improvement for using the cement by providing of rational grain composition of the components are presented.